POTENSI LIMBAH PADAT PERKEBUNAN KELAPA SAWIT DI PROVINSI RIAU - Novia Yanti, Rina; Hutasuhut, Ika Lestari (Wahana Forestra: Jurnal Kehutanan, 2020)
Oil palm plantations produce solid biomass waste, namely replanting stems, midribs, empty fruit bunches (EFB), shells and fruit fibers. In 2018 the area of ​​oil palm plantations in Indonesia reached 14.3 million ha and the area of ​​oil palm plantations in the Riau Province until 2018 was 2.7 million hectares. The availability of oil palm plantation waste in Riau Province, such as waste production in gardens and palm oil mill waste (PKS) needs to be studied further, so that the amount of oil palm biomass waste will be illustrated. The purpose of this study was to calculate the potential for biomass waste from oil palm plantations in the form of replanting stems, midribs, EFB, shells and fruit fibers. The method used in this study is calculating waste based on mass balance and the data were analyzed using linear regression. The results of this study indicate an increasing trend in the amount of waste produced. The most potential amount of waste is oil palm empty bunches (TKKS) of 6 663 956 tonnes per year on average.